2019
DOI: 10.1021/acsami.9b17664
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Packing, and Electrical Properties of New Regioisomeric n-type Semiconducting Molecules with Modification of Alkyl Substituents Position

Abstract: We design and synthesize a series of regioisomeric n-type small molecules, which have an identical diketopyrrolopyrrole (DPP) core and 2-(2,3-dihydro-3-oxo-1H-inden-1-ylidene)­propanedinitrile (INCN) terminal groups with octyl substituents at different positions. The isomeric structures are confirmed by two-dimensional NMR spectroscopy based on the heteronuclear multiple-bond coupling method. Incorporation of the electron-deficient DPP and strongly electron-withdrawing INCN groups yields deep frontier molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…16 Common molecular-level approaches to optimizing OPV thin film morphology and charge transport 17−19 include modifying the π-conjugated backbone structure and/or planarity and the structure and/or placement of solubilizing side chains. 20−24 Modifications specific to INCN-containing molecules include altering the solubilizing alkyl chain placement along the π-conjugated backbone 25 or on the indanone ring 26 and introduction of halogen atoms 27 or methoxy groups 28 structural changes, while sometimes seemingly minor, can induce a higher film absorption coefficient, larger crystalline coherence, and higher electron mobility, ultimately leading to higher PCE. We recently reported the ability of dicyanorhodanine (RCN) functionalized thiophenes to undergo Z/E configurational isomerization upon photoirradiation 29 and observed that the solid-state morphologies and optoelectronic properties of thin films from RCN-containing oligomers can be significantly affected by configurational composition.…”
mentioning
confidence: 99%
“…16 Common molecular-level approaches to optimizing OPV thin film morphology and charge transport 17−19 include modifying the π-conjugated backbone structure and/or planarity and the structure and/or placement of solubilizing side chains. 20−24 Modifications specific to INCN-containing molecules include altering the solubilizing alkyl chain placement along the π-conjugated backbone 25 or on the indanone ring 26 and introduction of halogen atoms 27 or methoxy groups 28 structural changes, while sometimes seemingly minor, can induce a higher film absorption coefficient, larger crystalline coherence, and higher electron mobility, ultimately leading to higher PCE. We recently reported the ability of dicyanorhodanine (RCN) functionalized thiophenes to undergo Z/E configurational isomerization upon photoirradiation 29 and observed that the solid-state morphologies and optoelectronic properties of thin films from RCN-containing oligomers can be significantly affected by configurational composition.…”
mentioning
confidence: 99%
“…As mentioned earlier, molecular packing, crystal structure, and the interplay between molecular structure and substrate surfaces have an important impact on the electrical properties of materials. 49 , 50 , 51 , 52 To gain insight into the correlation between the AlkCCMoid structure with its electrical properties we used 1-SC, 1-MP, and 1-SUB (onto Si/SiO 2 surfaces) to perform XRD, GIWAXS, and electrical measurements.…”
Section: Resultsmentioning
confidence: 99%
“…A thiophene spacer and DPP were chosen in this work because of a better reported performance in DPP- and TP-based small molecules . To study the difference between chalcogenopheno­[3,2 -b ]­pyrroles and thieno­[3,2- b ]­thiophene (TT), a 2-ethylhexyl side chain on DPP and methyl side chain on chalcogenopheno­[3,2- b ]­pyrroles was utilized to maintain sufficient solubility of the final molecules and retain the similarity of the donors. The pyrrole located at the end of the molecules minimizes the dihedral angle that may be generated by the pyrrole side chain. By studying these four molecules, we have, for the first time, investigated all reported chalcogenopheno­[3,2- b ]­pyrroles in the same system and compared them to thieno­[3,2- b ]­thiophene, thus obtaining insights into the differences between chalcogenopheno­[3,2 -b ]­pyrroles and TT at the molecular level.…”
Section: Introductionmentioning
confidence: 99%